Childhood Acute Post Streptococcal Glomerulonephritis in Far North Queensland. - Nderitu, Mercy; McDougall, Emma; Volkman, Thomas (Australian Journal of Rural Health, 2025)
Objective: To determine the recent incidence of paediatric Acute Post Streptococcal Glomerulonephritis in Far North Queensland and associated co‐occurring clinical conditions. Setting: Paediatric inpatient unit. Participants: Patients admitted to Hospital under 14 years of age meeting diagnostic criteria for APSGN between January 2015 and January 2020. Design: Single centre, retrospective observational analysis. Data and clinical information was extracted from electronic medical records. Case definitions were as specified in the Northern Territory guidelines for APSGN. Results: APSGN (n = 61) or probable APSGN (n = 4) was found in 65 of the 86 identified cases. Fifty‐five APSGN cases were identified as being Aboriginal and/or Torres Strait Islander, with the remaining 10 cases identifying as other ethnic groups. Mean annual incidence (0–14 years) was 27/100 000 person years. Aboriginal and/or Torres Strait Islander population incidence was 104/100 000 person years. Recurrent skin infection was noted in the majority of cases. Nineteen cases were lost to follow up; of these, 15 were from rural regions. Conclusions: A high incidence of childhood APSGN is present in Far North Queensland, with First nation's children overrepresented. This further adds to the national body of data on the disease, highlighting the necessity of an amplified response addressing the disease burden of group A Streptococcus and its main drivers, social disadvantage and remoteness. There is a need for enhanced surveillance and monitoring of the chronic sequelae of APSGN. Opportunities exist to amalgamate follow‐up practices across the region, and there is a need to enact reporting of the disease in Queensland.